1980
DOI: 10.1172/jci109782
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Synergistic Interactions of 3,5,3′-Triiodothyronine and the Adrenergic System in Stimulating Sugar Transport by Rat Thymocytes

Abstract: A B S T R A C T Isolated rat thymocytes were preincubated with various catecholamines, alone and together with 3,5,3'-triiodothyronine (T3), and the accumulation of the glucose analogues, 2-deoxy-D-glucose (2-DG) and 3-0-methylglucose (3-0-MG), was then measured. Epinephrine induced a time-and dose-dependent increase in the 15-min accumulation of 2-DG; at a concentration of 100 ,uM epinephrine, the effect was evident after a preincubation period of only 5 min. The lowest concentration of epinephrine at which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…DISCUSSION We have previously suggested that the T3-induced increase in the uptake of 2-DG and 3-0-MG by rat thymocytes in vitro reflects a primary action of thyroid hormone at the level of the plasma membrane that enhances the inward transport of sugar (1,2). The present studies, we believe, provide strong evidence for this view and shed light on the antecedent events that seem to be part of the mechanism of the T3 effect.…”
Section: Effects Of Alprenololsupporting
confidence: 74%
See 2 more Smart Citations
“…DISCUSSION We have previously suggested that the T3-induced increase in the uptake of 2-DG and 3-0-MG by rat thymocytes in vitro reflects a primary action of thyroid hormone at the level of the plasma membrane that enhances the inward transport of sugar (1,2). The present studies, we believe, provide strong evidence for this view and shed light on the antecedent events that seem to be part of the mechanism of the T3 effect.…”
Section: Effects Of Alprenololsupporting
confidence: 74%
“…In previous experiments, we have shown that T3 and epinephrine independently stimulate 2-DG uptake in rat thymocytes, and interact synergistically in this respect (1,2). Therefore, experiments were performed to compare the properties of the stimulatory response of the 2-DG uptake to epinephrine with those of the response to T3.…”
Section: Effects Of Adrenergic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that 3,5,3'-triiodothyronine (T3)' increases the uptake ofthe glucose analogue 2-deoxyglucose (2-DG) in isolated rat thymocytes in vitro (1)(2)(3)(4)(5). This effect of T3 is evident within 20 min after the addition of the hormones; it is independent of new protein synthesis, is calcium-dependent, and is mediated by an increase in cellular cyclic AMP (cAMP) concentration secondary to an increase in adenylate cyclase activity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the effect is rapid, is independent of new protein synthesis, and is mediated via an increase in cellular cyclic (c)AMP concentration, as a consequence of an increase in the activity of adenylate cyclase (2)(3)(4), an enzyme that resides within the plasma membrane. Furthermore, epinephrine, which is known to initiate its action upon binding to its plasma membrane receptors and thence activating adenylate cyclase, produces with T3 a synergistic increase in the 2-DG uptake (5 At the end of the incubation period, triplicate 250-Ml aliquots of reaction mixture were quickly removed and applied onto 0.3-um Millipore filters (Millipore Corp., Bedford, MA) under vacuum. The membranes were then quickly washed three times with 2.5 ml of ice-cold buffer.…”
mentioning
confidence: 99%